1984
DOI: 10.1042/bj2210261
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-induced increase in lactase activity and in immunoreactive lactase in adult rat jejunum

Abstract: Adult rats that had been fed on a low-starch high-fat diet for 7 days were force-fed with either the same diet or isoenergetic diets containing 40% of energy as either sucrose or lactose. Within 12 h, the increase in jejunal lactase activity in sucrose-and lactose-fed rats was accompanied by a corresponding increase in immunoreactive lactase protein.Activity of lactase in adult rat jejuno-ileum responds to increased intake of various carbohydrates, including starch and sucrose (McCarthy et al., 1980;Bustamante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…There are multiple reports of dietary-induced increases in intestinal lactase activity and enhanced lactose absorption with dietary manipulation [32,33]. Rat lactase protein expression can be induced by a lactose-rich diet [34]. Based on these reports, it is apparent that lactase is an adaptive enzyme that may be induced by lactose loading in animals.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple reports of dietary-induced increases in intestinal lactase activity and enhanced lactose absorption with dietary manipulation [32,33]. Rat lactase protein expression can be induced by a lactose-rich diet [34]. Based on these reports, it is apparent that lactase is an adaptive enzyme that may be induced by lactose loading in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude segmentale de la réponse peptidasique mesurée à l'aide du substrat phénylalanylglycine (Mc Carthy, Nicholson et Kim, 1980) (Yamada et al, 1983 ;Ulshen et Grand, 1979). Il semble cependant que l'activité lactasique intestinale soit rapidement (environ 12 h) modulable par un régime hyperglucidique (Goda et al, 1984). Enfin, soulignons le fait que la localisation de la réponse enzymatique le long de l'axe villositaire a été étudiée.…”
Section: Summary : Molecular Aspects Of Dietary Adaptation Of Pancreaunclassified
“…glucose or galactose) may be responsible for the age-related decline in the intestinal mucosal lactase activity (Goda, Bustamante, Thornburg & Koldovsky, 1984). In a previous communication to this Society it has been shown that continued supplementation of the diet of growing rats with physiological amounts of cow's milk or a 5 % solution of lactose had no effect on the decline of lactase with age (Tadesse, 1987).…”
Section: Pmentioning
confidence: 99%